2017
DOI: 10.1016/j.jfs.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Is there a gender effect on the cost of bank financing?

Abstract: In this paper, we address the question of whether the gender of a firm’s leader affects the cost of bank funding faced by small and medium enterprises in Europe. Using a large sample of observations of non-financial firms, during the years 2009–2013, we empirically test for the presence of discrimination, comparing female-led and male-led firms. After controlling for a rich set of variables and addressing potential endogeneity, our results show that i) female-led enterprises are more likely to face worse price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 73 publications
5
57
0
1
Order By: Relevance
“…Arzu and Mantovani (2016) showed that firms with higher rate of women in the board are more performing than ones with higher rate of men in the board. Nevertheless, the authors found that there are differences in the way credit is allocated relating to the gender of manager (Mascia & Rossi, 2017). Indeed, there are more firms led by women that do not receive credit, even if they deserve it because the presence of women in corporate leadership positions may improve firm performance (Noland & Moran, 2016;Lin, Pereira, Topalova & Turk, 2016).…”
Section: Women-run Firms' Credit Accessmentioning
confidence: 99%
“…Arzu and Mantovani (2016) showed that firms with higher rate of women in the board are more performing than ones with higher rate of men in the board. Nevertheless, the authors found that there are differences in the way credit is allocated relating to the gender of manager (Mascia & Rossi, 2017). Indeed, there are more firms led by women that do not receive credit, even if they deserve it because the presence of women in corporate leadership positions may improve firm performance (Noland & Moran, 2016;Lin, Pereira, Topalova & Turk, 2016).…”
Section: Women-run Firms' Credit Accessmentioning
confidence: 99%
“…On the supply side, the literature investigates whether women-led firms face lower credit availability and/or worse cost conditions and provides mixed evidence. 9 While some studies find that women-led enterprises have greater difficulties than man-led ones in obtaining bank loans (Marlow and Patton, 2005;Becker-Blease and Sohl, 2007;Muravyev et al, 2009;Bellucci et al, 2010;Kwong et al, 2012;Wu and Chua, 2012;Alsos and Ljunggren, 2016;Mascia and Rossi, 2017), others exclude gender discrimination and attribute the differences in cost conditions to economic and financial factors such as credit history, assets, sales, and years in business (Cavalluzzo et al, 2002;Blanchflower et al, 2003). A few papers find that women-led firms face more unfavourable loan contract terms than male firms, motivated by the fact that the formers are less inclined to grow (Fabowale et al, 1995).…”
Section: Gender and Bank Credit Accessmentioning
confidence: 99%
“…Indeed, the firm's leadership gender may not be completely exogenous. Either reverse causalitythe level of credit rationing may impact on the firm performance and, thus, on the choice of the leader to be hiredor omitted variables namely, unobservable organizational and managerial skills, or a given corporate culture may push towards a given leader rather than anothercan affect our estimates (see, inter alia, Adams and Ferreira, 2009;Liu et al 2014;Sila et al 2016;Mascia and Rossi, 2017). If this is the case, we cannot argue that our results are showing the existence of a causal relation between the leader's gender and the probability of non-application to bank credit.…”
Section: Addressing Endogeneitymentioning
confidence: 99%
See 2 more Smart Citations